2011
DOI: 10.1183/09031936.00115010
|View full text |Cite
|
Sign up to set email alerts
|

Farming in childhood, diet in adulthood and asthma history

Abstract: The decrease in the number of children living on traditional farms in France during early childhood and changes in diet could both play a role in the increase in asthma prevalence over the last decades. This study aimed to assess 1) the association of farming lifestyle in childhood and asthma, and 2) whether diet in adulthood modifies the association between farming lifestyle in childhood and adult-onset asthma.In the French Etude Epidemiologique des Femmes de la Mutuelle Générale de l'Education Nationale (E3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The role of environmental and behavioral factors might differ across these phenotypes. In childhood, several environmental factors have been reported to be associated with asthma, including a protective effect of farming environment early in life or prenatally [13][14][15], a deleterious effect of exposure to second hand smoke, as well as a deleterious effect of exposure to air pollution [13,[15][16][17][18][19]. The conclusions of a recent review on the induction of asthma and the environment [17] provide scientific support for public health efforts to limit in utero and postnatal exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of environmental and behavioral factors might differ across these phenotypes. In childhood, several environmental factors have been reported to be associated with asthma, including a protective effect of farming environment early in life or prenatally [13][14][15], a deleterious effect of exposure to second hand smoke, as well as a deleterious effect of exposure to air pollution [13,[15][16][17][18][19]. The conclusions of a recent review on the induction of asthma and the environment [17] provide scientific support for public health efforts to limit in utero and postnatal exposure to tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding domestic exposures, household help which is strongly related to SES, has not been taken into account until now. Diet, an important aspect of lifestyle, is also linked to social factors [14]. Recent studies suggested that low SES plays a role in both childhood-and adult-onset asthma [15].…”
Section: Interrelationship Between Environmental and Behavior Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, some aspects in early life appear to protect against the development of asthma. In children, contact with livestock and being born and raised on a farm reduces the risk of asthma in adulthood [28][29][30]. Similar to viruses, it is unknown whether the bacterial colonisation acts as the environmental trigger in genetically predisposed persons or whether this colonisation is merely a marker of the underlying genetic asthmatic constitution.…”
Section: Childhood-onset Asthmamentioning
confidence: 99%
“…A high exposure to innate immunity-stimulating molecules, such as TLR agonists, is probably needed to prompt this beneficial effect [24]. Being conceived and raised in a farming environment appears to have a beneficial effect that persists at least into later childhood [25,26] and may therefore provide a healthy lifestyle for those at risk of developing allergic asthma. Pharmaceutical agonists of TLR4, TLR7, TLR8 and TLR9 have been developed to treat or prevent allergic disease, and have been tested in clinical studies.…”
Section: Early Immune Maturation and Respiratory Healthmentioning
confidence: 99%